Caravaggio's 'Seven Works of Mercy' in Naples. The relevance of art history to cultural journalism - Bühren, Ralf van (Church, Communication and Culture, 2017)
The artistic heritage of the Catholic Church still attracts attention all over the world. For almost 2000 years, it has provided aesthetic access to spiritual meaning, together with the Church's text communication, both spoken and written. Christian art and architecture, therefore, rank among the oldest communication media. Even today, they can empower a culture of reflection and high-content communication. This article about Caravaggio explains why Christian art offers opportunities for religious correspondents, Church media relations, as well cultural and arts journalists.